Tionghoa di Caruban Nagari : Peranan Tionghoa dalam Membentuk Lanskap Sejarah Cirebon - Rizky Riyadu Taufiq (Jurnal Identitas, 2024)
The early development of Cirebon was marked by the arrival of Chinese communities, particularly during the expeditions of Zheng He in the 15th century. Various sources indicate that even before the establishment of the Cirebon Sultanate, the northern coastal region of Java had already become a destination for Chinese diaspora. Archaeological findings such as a shipwreck off the coast of Cirebon and the sites of Tamanan and Dingkel Sambimaya in Indramayu serve as early evidence of their presence. This study employs historical methodology, encompassing heuristic, source criticism, interpretation, and historiographical writing. Archaeological and philological approaches are applied to present stronger evidence of the Cirebon– Chinese relationship. The study reveals three major findings: First, the Chinese community played a central role in the development of physical infrastructure and cultural arts, as seen in relics such as the lighthouse at Muara Jati, the architecture of palaces and mosques, the mega mendung batik motif, and royal carriages like Singa Barong and Paksinagaliman in the Kasepuhan and Kanoman palaces. Second, deeper relationships developed through intermarriage and involvement in governance. Notable examples include the marriage of Sunan Gunung Jati and Princess Ong Tien of China, as well as the appointment of Chinese figures to strategic positions such as the head of Indramayu port and as supervisors in the construction of the Sunyaragi Cave Garden. Third, archaeological and philological legacies reinforce the narrative of Chinese involvement, such as the Panjunan Red Mosque, Dewi Welas Asih Vihara, Sang Ciptarasa Great Mosque, Talang Temple, and textual sources like Negarakertabhumi, Carita Purwaka Caruban Nagari, and Sejarah Rante. These sources collectively affirm the significant role of the Chinese community in the cultural acculturation, spread of Islam, and historical development of Cirebon.